Storage-Transmission Joint Planning Method to Deal with Insufficient Flexibility and Transmission Congestion - Yang, Xiuyu; Chai, Guofeng; Liu, Xueyuan; Xu, Minghong; Guo, Qi (Frontiers in Energy Research, 2021)
The insufficient power system flexibility and transmission congestion are two fundamental reasons for wind power curtailment. In the power system which the scale of wind power is growing rapidly, the two factors of wind power curtailment events coexist and have a certain coupling relationship. The configuration of the energy storage system not only can increase the flexibility of the system but also alleviate transmission congestion. Therefore, the joint planning of energy storage and transmission grid that takes into account the flexibility of the system and the transmission congestion is of great significance to solve the wind curtailment. Hence, this paper first decouples the insufficient flexibility and transmission congestion wind power curtailment, quantitatively analyzes the impact of transmission capacity on the coupling relationship between the two; second, reveal the principle of joint planning of energy storage system and transmission congestion, and construct an optimization model, and propose to set up the capacity of the wind power which connects the power network. The flow of solution, which deals with grid planning first and the energy storage system optimization, not only ensure the accuracy of it but also reduce the calculation greatly. Finally, a case study of a wind power base in Northeast China and an improved Garver-6 system is carried out to verify the effectiveness of the method.